Sustainability of Technology Use in Higher Education in Indonesia Post the COVID-19 Pandemic: Analysis of Scientific Evidence - Gunawan Widjaja (Indonesian Journal of Education (INJOE), 2022)
We carried out this study to analyze several scientific pieces of evidence on the sustainability of the use of technology in the context of post-pandemic higher education learning. We got several kinds of literature in the form of scientific evidence from several publications released between 2010 and 2020, which we obtained electronically with keyword-based searches such as “technology uses," "sustainability Education," higher education" post-Covid-19," and technology in learning." To get answers to the questions of this study, we analyzed the data under another phenomenon approach which involved data coding techniques, data evaluation, data interpretation, and valid and reliable conclusions. Based on existing data and discussion of the results, we can conclude that the analysis of scientific evidence shows that the continued use of technology in teaching in higher education is an effort made to harmonize learning in the 21st century, which prioritizes technology adoption to accelerate learning outcomes in tertiary institutions. This result will be a helpful insight into the following studies